Antibiotic prescribing practices and antibiotic use quality indicators in Luang Prabang, Lao PDR: a point prevalence survey in a tertiary care hospital - Elias, C; Ha, NT; Sengvilaipaserth, O; Phaychith, A; Chansamouth, V; Phongsavath, V; Keohavong, B; Detleuxay, K; Maniphonh, P; Soukhaseum, T; Vanhems, P; Babin, F (BioMed Central, 2024)
Context: The increase and global dissemination of antibiotic resistance limit the use of antibiotics to prevent and treat infections. Implementing antibiotic stewardship programs guided by local data on prescription profiles is a useful strategy to reduce the burden of antibiotic resistance. The aim was to determine the prevalence of antibiotic use and guideline compliance at Luang Prabang provincial hospital, Lao PDR. Methods: A point prevalence survey of antibiotics was conducted among hospitalized patients admitted to Luang Prabang hospital (204 beds) in Lao PDR on May 25, 2023. All patients presenting at 8:00 AM were eligible. Sociodemographic data, indications for antibiotic use, and antibiotic prescriptions were collected from medical records using a paper-based questionnaire and entered into an electronic platform following WHO methodology. The prevalence of antibiotic use was determined. Results: Out of the 102 patients included, 60(58.8%) were undergoing antibiotic treatment, of which 33(55.0%) received combination therapy, and 7(10.5%) had two indications for antibiotic use. The highest prevalence was in the surgical ward (14/15, 93%) followed by general paediatrics (18/27, 67%). Out of the 100 antibiotic prescriptions, 47(47%) were for community-acquired infections, 26(26%) for surgical prophylaxis, 13(13%) for hospital-acquired infections and 5(5%) for medical prophylaxis. Twenty(20%) antibiotics were prescribed for obstetrics and gynaecology prophylaxis, 17(17%) for intra-abdominal infections, and 10(10.0%) for pneumonia treatment as well as bone, and joint infections. The main antibiotics prescribed were ceftriaxone 36(34.6%), metronidazole 18(17.3%), ampicillin 8(7.7%), and gentamicin 8(7.7%). Only 2(3%) samples were sent to the laboratory, one of which showed a positive culture for Escherichia coli Extended Spectrum β-Lactamase. According to the WHO Access Watch and Reserve classification, 55(52.9%) molecules belonged to the Access category, 47(49.1%) to the Watch category, and none to the Reserve category. Only 14.9% of antibiotic prescriptions were fully compliant with current guidelines. Conclusion: This study indicated a significant prevalence of antibiotic use and a very low compliance with guidelines at Luang Prabang provincial hospital, Lao PDR. This highlights an urgent need for comprehensive strategies at all levels to optimize antibiotic use in hospitals, emphasizing diagnostic improvements, and continued research to address the factors driving this excessive antibiotic usage and improve adherence to guidelines.